1982
DOI: 10.1111/j.1365-2133.1982.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased respiratory burst activity of monocytes and polymorphonuclear leukocytes in psoriasis

Abstract: We studied the respiratory burst activity of peripheral blood monocytes and polymorphonuclear leukocytes (PMN) in eleven patients with psoriasis and eleven healthy controls, using zymosan particles to activate the phagocytes in vitro. The activation of the phagocytes was measured in a luminol-enhanced chiluminescence (CL) assay. We found a significantly higher respiratory burst activity of both monocytes and PMN in patients with psoriasis compared with the control subjects. The percentages of monocytes in psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Exper imental studies revealed close correlations between the central bone marrow pool, the monocyte system, and the tissue-fixed mac rophages. Therefore, results obtained in studying monocytes are comparable to those obtained in tissue-fixed macrophages [6], Signs of activation of monocytes, i.e., macro phages of blood, could be detected by in vitro experiments [3,16,24], Using a skilful in vi vo test system developed by Munz et al [19][20][21][22], we tried to find out if there is any functional alteration of tissue-fixed macro phages in psoriatics.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Exper imental studies revealed close correlations between the central bone marrow pool, the monocyte system, and the tissue-fixed mac rophages. Therefore, results obtained in studying monocytes are comparable to those obtained in tissue-fixed macrophages [6], Signs of activation of monocytes, i.e., macro phages of blood, could be detected by in vitro experiments [3,16,24], Using a skilful in vi vo test system developed by Munz et al [19][20][21][22], we tried to find out if there is any functional alteration of tissue-fixed macro phages in psoriatics.…”
supporting
confidence: 61%
“…According to the thesis of van Furth [6] that tissue-fixed macrophages and blood monocytes belong to the unitary mononuclear phagocyte sys tem, investigations on sessile macrophages and blood monocytes are comparable. A nonspecific activation of blood monocytes in psoriatics could be revealed in vitro [3,16,24]. Polymorphonuclear leukocytes were found to be activated as well: increased chemotaxis [5,14,17,26], phagocytosis [26] and respiratory burst-activity [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We were inter ested in studying the production of superoxide anion by psoriatic and normal dermal fibro blasts since in psoriasis the respiratory burst activity of monocytes and polymorphonuclear (PMN) leukocytes is increased [12], and acti vated PMN neutrophilic granulocytes play an important role in certain inflammatory skin disorders, particularly in psoriasis [13,14], The metabolic activation of PMN is associated with the release of reactive oxygen species (ROS), such as superoxide anion (CL-), hydro gen peroxide (FLCL), hydroxyl radical (OH) and singlet oxygen [15]. The exact cellular mechanisms involved in the production of ROS by PMN are not fully understood; how ever, there are certain features which allow an insight into complex processes [ 16].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue damage caused by reactive oxygen species (ROS) such as EECU and Oj" has been implicated in the pathogenesis of a number of inflammatory diseases including rheumatoid arthritis [1], psoriasis [2] and some forms of dermatitis [3,4], In rheumatoid arthritis ROS are formed during hypoxia-reperfusion cycles [5], which also occur in heart and kidney transplantation [6]. It has been reported [7] that y-hydroxybutyrate protects the intestine of the hamster from ROS-initiated tissue damage induced after 30 min of hypoxia, fol lowed by 3 h of reperfusion.…”
Section: Introductionmentioning
confidence: 99%